Convergence in Nutritional Interventions in India: Enablers and Inhibitors (Journal of Advanced Research in Social Sciences, 2025)
Malnutrition is a multifaceted problem needing a multisectoral response to draw upon synergies across policies and programs. It remains one of the most serious public health challenges. Decades of policy and programmatic efforts have been made to tackle the continuing challenge of malnutrition. However successful implementation of these programs needs inter-departmental convergence, especially at the village level. Therefore, research was undertaken using a mixed method design with the objective of exploring the existing convergence through Village Health, Sanitation and Nutrition Days (VHSNDs) in selected tribal blocks of Maharashtra. Data was collected from frontline workers (FLWs), with service users and VHSNDs were observed. The study provides evidence-based practices of convergence among health and nutrition department and assess the applicability of the strategies formulated under the National Nutrition Mission (NNM) in tribal areas from the state of Maharashtra in India. It would inform policy makers about the enablers and inhibitors of implementing nutritional interventions to address systemic gaps.